2008
DOI: 10.1089/hum.2008.016
|View full text |Cite
|
Sign up to set email alerts
|

Kallikrein-Modified Mesenchymal Stem Cell Implantation Provides Enhanced Protection Against Acute Ischemic Kidney Injury by Inhibiting Apoptosis and Inflammation

Abstract: Mesenchymal stem cells (MSCs) migrate to sites of tissue injury and serve as an ideal vehicle for cellular gene transfer. As tissue kallikrein has pleiotropic effects in protection against oxidative organ damage, we investigated the potential of kallikrein-modified MSCs (TK-MSCs) in healing injured kidney after acute ischemia/reperfusion (I/R). TK-MSCs secreted recombinant human kallikrein with elevated vascular endothelial growth factor levels in culture medium, and were more resistant to oxidative stress-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(31 citation statements)
references
References 49 publications
(60 reference statements)
2
27
0
Order By: Relevance
“…Transplantation of MSCs has proven to be an effective treatment for tissue injuries, including myocardial infarction, 5) hind limb ischemia, 6) acute renal failure 7) and liver transplantation. 8) However, progress in stem cell therapy is hampered by the poor survival of the implanted cells.…”
mentioning
confidence: 99%
“…Transplantation of MSCs has proven to be an effective treatment for tissue injuries, including myocardial infarction, 5) hind limb ischemia, 6) acute renal failure 7) and liver transplantation. 8) However, progress in stem cell therapy is hampered by the poor survival of the implanted cells.…”
mentioning
confidence: 99%
“…This was due to an increase in cell proliferation due to differentiation of some transplanted BMMNC into renal tubular epithelial cells in addition to an increase in biological activity, due to release of various growth factors and trophic factors. Hagiwara et al [57] similarly showed that using kallikrein-modified MSC (TK-MSC; combined SC and kallikrein gene approach) led to the migration and homing ability as well as paracrine effect, thereby enhanced renal protection and advanced benefits in healing the injured kidney. The expression of human tissue kallikrein in the rat kidney after TK-MSC implantation exhibited enhanced protection against renal injury by inhibiting apoptosis and inflammatory cell infiltration.…”
Section: Evidence Favouring Sc In Renal Irimentioning
confidence: 99%
“…Thus TK-MSC secreted recombinant human tissue kallikrein into culture medium and significantly improved stem cell survival during oxidative stress via activation of the phosphatidylinositol 3-kinases/protein kinase B (PI3K-Akt) pathway. At 48 h after IRI, TK-MSC inhibited interstitial neutrophil and monocyte/macrophage infiltration and decreased the myeloperoxidase activity, superoxide formation, p38 mitogen-activated protein kinase phosphorylation and expression of TNF-α, monocyte chemoattractant protein-1 and ICAM-1 [57]. Wang et al [58] showed improved renal function when SC of neural origin (neural precursor cells, NPC) were administered in the rat IRI model.…”
Section: Evidence Favouring Sc In Renal Irimentioning
confidence: 99%
“…Kallikrein is a renoprotective molecule due its anti-inflammatory, -apoptotic and -dilation activities. When delivered to kidneys of rats in a renal ischemia/reperfusion injury model by modified MSCs caused a decrease in blood urea nitrogen and creatine levels and the number of apoptotic kidney cells and inflammatory cells within the kidney [152] . While these studies demonstrate the various and numerous potential factors for the enhancement of MSC-dependent treatment of acute myocardial infarctions and other ischemic injuries, it seems likely the best approach will be a combination of molecules that target the cells appropriately and regulate both the paracrine stimulation of surrounding cells and the differentiation of the transplanted MSCs.…”
Section: Cardiovascular and Ischemic Diseasementioning
confidence: 99%